Identifikasi Kesulitan Siswa dalam Menyelesaikan Soal HOTS Ditinjau dari Teori Polya - Shabrina Khilda Zulfia; Diana Ermawati; Fitriyah Amaliyah (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
Students' Mathematical Problem Solving Ability in solving HOTS problems is still low because it is considered difficult and rarely taught in schools, therefore students often answer directly without analyzing and determining a solution strategy. The purpose of this study is to describe students' difficulties in solving HOTS problems in terms of Polya's theory. This study uses a qualitative research method using a case study approach. The subjects in this study were 9 students, 3 students in the low category, 3 students in the medium category, and 3 students in the high category. Data collection techniques used were observation, interviews, and documentation. Based on the results of the analysis of the difficulties experienced by students include difficulty writing information, difficulty writing formulas, errors in calculations, and not drawing conclusions. It can be concluded that low category students have difficulty at the stage of understanding the problem, medium category students have difficulty at the stage of implementing the plan, and high category students have difficulty at the stage of drawing conclusions. Based on the results of the study, in further research, appropriate strategies can be carried out to overcome students' difficulties in solving HOTS problems.